Synthetic genomics in crop breeding: Evidence, opportunities and challenges - Yuhan Zhou; Ziqi Zhou; Qingyao Shu (Crop Design)
Synthetic genomics represents a formidable domain, encompassing the intentional design, construction, and manipulation of artificial genetic material to generate novel organisms or modify existing ones. In the context of crop breeding, molecular design breeding has emerged as a transformative force, ushering in notable progress. Nevertheless, the field faces unprecedented challenges, with climate change, population growth, and the scarcity of superior genetic resources exerting significant pressures. Recent strides in DNA synthesis methodologies, exemplified by innovative techniques like SCRaMbLE, have empowered the assembly and engineering of viral and microbial genomes. These advancements open promising avenues for the application of synthetic genomics in multicellular eukaryotic organisms, particularly in the realm of crop improvement. Synthetic genomics, with its capacity to manipulate gene sequences and regulatory elements, holds immense promise for the breeding of crops that meet diverse needs. Despite these advancements, the integration of synthetic genomics into crop breeding encounters hurdles, including the intricacies of complex crop genomes, the unpredictability introduced by epigenetic modification, and the limitations in achieving robust transformation processes. Addressing these challenges is pivotal to unlock the full potential of synthetic genomics in revolutionizing crop breeding. Looking ahead, we envision synthetic genomics in crop breeding not only as a scientific frontier but also as a burgeoning industry.